A new addition to the Helvella macropus group (Helvellaceae) from Southwestern China - Li, Tai-Shun; Zhou, De-Qun; Zhao, Qi; Zhang, Ying (Phytotaxa, 2023)
Based on the morphology and phylogenetic analyses of 5.8s ribosomal RNA and internal transcribed spacer 2 (ITS), large subunit rRNA (LSU), translation elongation factor-1 alpha (tef-1α), and heat shock protein 90 (hsp90), a novel species, Helvella submacropus is introduced. The species is found in Yunnan Province, China, and is characterized by shallowly cupulate to cupulate apothecia with villose to densely pubescent receptacle surface and cylindrical stipes. The phylogenetic analyses showed that H. submacropus clustered with H. macropus and H. guttata. However, these three species can be well distinguished by morphological and molecular evidence. The taxonomic description, illustration, and phylogeny of H. submacropus, and also its comparison with similar taxa are provided.